(untitled) (Vietnam Journal of Community Medicine, 2023)
Background: Working motivation is employees’ desire and willingness to work to achieve organizational goals. For medical facilities, the working motivation of medical staff affects the quality of medical service delivery. Objective: Describe the working motivation of health workers at the National Hospital of Endocrinology in 2022. Methods: Cross-sectional study, quantitative research. Results: From the analysis of quantitative information from 520 health workers at the National Hospital of Endocrinology through questionnaires, the research results show that 28.1% of health workers have high work motivation, and 71.9% of health workers have usual work motivation. The typical average score of work motivation of health workers is 3,89±0,44, which is relatively high, from 3.82 to 3.97 (maximum score is 5).